Towards a Metamodel for a Requirements Engineering Process of Embedded Systems - Pereira, Tarcísio; Albuquerque, Deivson; Sousa, Aêda; Alencar, Fernanda; Castro, Jaelson (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2016)
In the embedded systems (ES) area, more than 50% of problems occur at system delivery and are related to misconceptions in capturing requirements. According to our systematic literature review (SLR), no evidence explicitly depicts how an embedded system must be elicited and specified. However, understanding the embedded systems and their environment is a strenuous activity. Even though current approaches present some contributions, the definition of a systematic requirements engineering process remains a challenging issue. Based on this shortcoming, we developed a metamodel that defines concepts and relationships that must be taken into account the development of an ES. From the metamodel, we define a precise requirements engineering process. This research presents the main results of a SLR, a resource model, and a sketch of a process to guide the requirements development of embedded systems.